Reliabe Data Link for Power Transfer Control in an Inductive Charging System for Electric Vehicles - Sanftl, Benedikt; Joffe, Christopher; Trautmann, Martin; Weigel, Robert; Kölpin, Alexander (IEEE MTT-S International Conference on Microwaves for Intelligent Mobility, 2016)
This paper presents a novel data link for electric vehicles charged through inductive power transfer (IPT) systems. The data link uses the magnetically coupled coils as transmission medium. The data link is intended to transfer the instantaneous current and voltage values in the power receiving circuitry on the EV platform. One key goal is to enable robust and reliable communication for closed-loop operation of the IPT system. By careful system design the data link can be used in the noisy environment of the power transfer. For the communication architecture a fully digital approach is considered. The digital signal processing is done in an industrial controller thus, the data link can be implemented into existing systems with minimum changes. For proof of concept the communication system is connected to a 3 kW IPT system and evaluated. These key performance values for simultaneous power transfer and communication will be presented. The data link stands out with its high signal to noise ratio and error vector magnitude, consequently high reliability can be guaranteed.
elib2cris::1512001600,sanftl2016